The AMerican PREGNANcy Mother–Child CohorT: description and prevalence of baseline outcomes and medication dispensing - Leal, Lisiane F.; Sheehy, Odile; Gorgui, Jessica; Bérard, Anick (Frontiers in Pharmacology, 2025)
PurposeThis study aims to present the AMerican PREGNANcy Mother–Child CohorT (AM-PREGNANT) and its maternal and linked-child characteristics.MethodsAM-PREGNANT was built using the Merative™ MarketScan® Commercial Database. We updated and implemented a hierarchical algorithm using ICD-9-CM and ICD-10-CM codes to identify pregnancies in individuals aged 15–45 years (2003–2021). A unique family identifier linked mothers to their children. Enrollment required continuous coverage for 90 days before, during, and 42 days after pregnancy for the mothers and 1 year after birth for the linked children. Pregnancy outcomes were categorized as deliveries, spontaneous abortions, and induced abortions. We characterized AM-PREGNANT (2004–2020) by sociodemographic factors, pregnancy history, comorbidities, and medication dispensing by pregnancy outcome. Medication dispensing, identified through filled prescriptions using drug claims, was analyzed for the 90 days before pregnancy until the last menstrual period (LMP), throughout pregnancy, and from delivery through the postpartum period. Linked children were assessed for low birth weight (LBW), preterm birth, congenital malformations, and other characteristics. Maternal and gestational age distributions were compared with United States (US) national estimates.ResultsWe identified 7,991,200 pregnancies from 6,079,647 persons (2003–2021). Applying continuous enrollment criteria and restricting the study period to 2004–2020 resulted in 4,767,208 pregnancies. Of these, 76.9% resulted in deliveries, 17.3% were spontaneous abortions, and 5.9% were induced abortions. The established linked mother–child cohort comprises 2,578,990 pregnancies. The mean maternal age in the linked mother–child cohort was 30.4 years (SD, 5.4). The mean gestational age at delivery was 38.6 weeks. Infections were the most prevalent maternal comorbidity (11.8%). Among deliveries, the prevalence of medication dispensing in mothers before, during, and after pregnancy were 63.2%, 88.7%, and 82.9%, respectively. Among linked children, 52.1% were male, 12.0% were preterm, and 4.5% had low birth weight. The prevalence of major congenital malformations was 13.1%. The characteristics of children with continuous enrollment were similar to those without, except for medication dispensing during the first year of life (62.9% vs. 45.6%). Both maternal and gestational age distributions of AM-PREGNANT were comparable to the US national estimates.ConclusionAM-PREGNANT is a valuable cohort for studying medication safety in mothers and children. Strict enrollment criteria ensured reliable data, minimizing the risk of misclassification. This cohort is a key resource for multi-country perinatal pharmacoepidemiological studies.